Analisis Peningkatan Literasi Keuangan, Komunitas Investasi Dan Sekolah Pasar Modal Terhadap Kemudahan Investor Berinvestasi Di Pasar Modal - Moh. Fathur Rozi; Jeni Susyanti; Ety Saraswati (UNIVERSITAS ISLAM MALANG, 2021)
Abstract Indonesia is predicted to have the 4th largest GDP in the world by 2050. One of the major contributors to GDP is investment. Based on KSEI data (2020) the number of investors in Indonesia is still 3.27 million investors or 1.73% of the total productive age population. This proves that Indonesia still needs encouragement to become the country with the 4th largest GDP in the world. The purpose of this study was to determine whether there is an influence between financial literacy, investment community and capital market schools on the ease of investing. The method used is quantitative with a survey approach. The results show that there is an influence between financial literacy, the investment community and the capital market on the ease of investing, which means that if there is an increase in financial literacy, the investment community and capital market schools, there will also be an increase in the ease of investing. Keywords: Financial Literacy, Comunity Investment, Capital Market School, Easy To Invest